Active tectonics of the east Alborz mountains, NE Iran: Rupture of the left-lateral Astaneh fault system during the great 856 AD Qumis earthquake - Hollingsworth, J; Nazari, H; Ritz, J; Salamati, R; Talebian, M; Bahroudi, A; Walker, RT; Rizza, M; Jackson, J (2010)
The 856 A.D. Qumis earthquake (M7.9) is the most destructive earthquake to have occurred in Iran, killing more than 200,000 people and destroying the cities of Damghan and the old Parthian capital of Shahr-i Qumis (Hecatompylos). This study combines evidence of historical seismicity with observations of the geomorphology and paleoseismology to provide the first detailed description of active faulting in the Damghan region of the east Alborz mountains, Iran. Regional left-lateral shear is accommodated on the Astaneh, Damghan, and North Damghan faults. Quaternary alluvial fans have been displaced along the Astaneh fault, with 15-20 m stream offsets recording the cumulative displacement over the last two to five earthquakes. A paleoseismology study from a single trench along a 5-10 km segment of the Astaneh fault reveals a rupture prior to 1300 A.D. and significantly later than 600 B.C. Despite the limitations of a single trench in documenting the spatial and temporal evolution of the fault over the late Quaternary, we are nevertheless able to bracket the last event to a time period consistent with the 856 A.D. earthquake. Two older earthquakes were also identified during the Holocene occurring between 600 B.C. and 4600 B.C. and between 4600 B.C. and 9600 B.C. The location of our trench within a bend on the Astaneh fault, which could act as a barrier to rupture propagation, means the three earthquakes recovered from our trench over the Holocene may represent a minimum. Further trenching will reveal how the Astaneh fault ruptures over repeated earthquakes and, consequently, the magnitude and extent of slip during the 856 A.D. earthquake. Copyright 2010 by the American Geophysical Union.